Quantification of training load relative to match load of youth national team soccer players - Szigeti, G.; Schuth, G.; Revisnyei, P.; Pasic, A.; Szilas, A.; Gabbett, T.; Pavlik, G. (Sports Health: A Multidisciplinary Approach, 2022)
Background: Previous studies have examined the training load relative to match load in club settings. The aims of this study were to (1) quantify the external training load relative to match load in days before a subsequent international game and (2) examine the cumulative training load in relation to match load of U-17 national team field soccer players. Hypothesis: Volume and intensity load parameters will vary between trainings; the farthermost trainings have the highest load gradually decreasing toward the match. Study Design: Prospective cohort study. Level of Evidence: Level 4. Methods: External training load data were collected from 84 youth national team players using global positioning technology between 2016 and 2020. In the national team setting, training load data were obtained from 3 days before the actual match day (MD-3, MD-2, MD-1 days) and analyzed with regard to the number of days up to the game. Volume and intensity parameters were calculated as a percentage of the subsequent match load. Results: Significant differences were found between MD-1 and MD-2, as well as between MD-1 and MD-3 for most volume parameters (P < 0.01; effect sizes [ESs] 0.68-0.99) and high-intensity distance (P < 0.002; ES 0.67 and 0.73) and maximum velocity (P < 0.002; ES 0.82) as intensity parameters. Most cumulative values were significantly different from total duration (P < 0.001, common language ES 0.80-0.96). Conclusion: The training volume gradually decreased as match day approached, with the highest volume occurring on MD-3. Intensity variables, such as maximum velocity, high-intensity accelerations, and meterage per minute were larger in MD-1 training relative to match load. Training volume was lowest in MD-1 trainings and highest in MD-3 trainings; intensity however varies between training days. Clinical Relevance: The findings of this study may help to understand the special preparational demands of international matches, highlighting the role of decreased training volume and increased intensity.